Où en sont les études sur le livre de Qohélet (2018–2020) ? - Lavoie, Jean-Jacques (Studies in religion, 2022)
In this article, the author presents, in nine parts, fourteen books on the text of Qohelet published recently. These nine parts correspond to nine important themes : the methodology, the date and place of writing of Qohelet’s book, the language of the book, foreign influences, references to the Bible and to apocalyptic thought, allusions to specific historical circumstances, the structure of the book, the explanation about apparent or real contradictions, and the meaning of the word hbl.